Lausannevirus, a giant amoebal virus encoding histone doublets - Thomas, Vincent; Bertelli, Claire; Collyn, François; Casson, Nicola; Telenti, Amalio; Goesmann, Alexander; Croxatto, Antony; Greub, Gilbert (Environmental microbiology, 2011)
Summary Large viruses infecting algae or amoebae belong to the NucleoCytoplasmic Large DNA Viruses (NCLDV) and present genotypic and phenotypic characteristics that have raised major interest among microbiologists. Here, we describe a new large virus discovered in Acanthamoeba castellanii co‐culture of an environmental sample. The virus, referred to as Lausannevirus, has a very limited host range, infecting Acanthamoeba spp. but being unable to infect other amoebae and mammalian cell lines tested. Within A. castellanii, this icosahedral virus of about 200 nm exhibits a development cycle similar to Mimivirus, with an eclipse phase 2 h post infection and a logarithmic growth leading to amoebal lysis in less than 24 h. The 346 kb Lausannevirus genome presents similarities with the recently described Marseillevirus, sharing 89% of genes, and thus belongs to the same family as confirmed by core gene phylogeny. Interestingly, Lausannevirus and Marseillevirus genomes both encode three proteins with predicted histone folds, including two histone doublets, that present similarities to eukaryotic and archaeal histones. The discovery of Lausannevirus and the analysis of its genome provide some insight in the evolution of these large amoebae‐infecting viruses.